Assessing the Efficacy of Peripheral Nerve Blocks in Predicting Functional Recovery Post-Nerve Reconstruction after Limb Amputation - Muhammad Qaiser Faheem, Samreen Mushtaq, Asad Shameem, Mobasher Ahmad Saeed, Abrar Ul Hassan Pirzada, Abdur Rauf Hammad (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Predicting neurological and functional recovery after nerve reconstruction in amputated limbs remains a major clinical challenge. Early response to peripheral nerve block (PNB) may offer a simple, non-invasive method to assess underlying nerve viability and forecast long-term outcomes. Objective: To evaluate the efficacy of early PNB response in predicting sensory, motor, and functional recovery following peripheral nerve reconstruction in traumatic limb amputation patients. Methods: This prospective observational study was conducted at Social Security Hospital Shahdara, Lahore, and POF Hospital Wah Cantt from February 2022 to March 2023. A total of 100 patients undergoing reconstructive nerve surgery were assessed. Early response to ultrasound-guided PNB was recorded at 15 and 30 minutes. Motor recovery (MRC scores), sensory recovery (two-point discrimination, monofilament testing), electrophysiological reinnervation, and functional outcomes (DASH/LEFS scores) were evaluated at 1, 3, and 6 months. Pearson correlation analysis assessed associations between early block response and long-term recovery. Results: Sixty-three patients (63%) were early responders. Early responders demonstrated significantly better motor recovery at six months (4.09 ± 0.82 vs. 2.92 ± 1.14; p = 0.001) and superior sensory outcomes (p < 0.001). Functional disability scores improved markedly in responders (DASH p < 0.001; LEFS p = 0.002). Early PNB response showed strong correlations with motor recovery (r = 0.71, p < 0.001), sensory improvement (r = 0.65, p = 0.002), and functional outcomes (r = 0.68, p < 0.001). Conclusion: Early clinical response to peripheral nerve block is a strong predictor of neurological and functional recovery after nerve reconstruction in amputated limbs. PNB responsiveness should be incorporated into preoperative evaluation to optimize surgical planning and rehabilitation strategies. Keywords: Peripheral nerve block, nerve reconstruction, limb amputation, functional recovery, sensory reinnervation, MRC score, DASH, LEFS.